A Comparison of Landraces vs. Modern Varieties of Lettuce in Organic Farming During the Winter in the Mediterranean Area: An Approach Considering the Viewpoints of Breeders, Consumers, and Farmers - Missio, Joan Casals; Rivera, Ana; Figàs, Maria Rosario; Casanova, Cristina; Camí, Borja; Soler, Salvador; Simó, Joan (Frontiers in Plant Science, 2018)
The interest of farmers in growing lettuce landraces is increasing, as landrace varieties prove particularly appealing to consumers striving to purchase natural, local and high-quality produce. Although high genetic diversity exists in the landrace gene pool, this has scarcely been studied, thus hindering landrace utilisation in agriculture. In this study we analysed the genetic diversity and the agronomic and quality traits of lettuce landraces in organic agrosystems, by characterising 16 landraces and 16 modern varieties. We compared 29 morphological descriptors, and several traits relating to agronomic behaviour (total and commercial weight, resistance to B. lactucae) and quality (colour, chlorophyll, dry matter, and total sugars). Trials were conducted in two localities and managed following organic farming practices. Moreover, farmers and consumers participated in the phenotyping of accessions by scoring yield, resistance to B. lactucae, appearance and taste acceptance. Results show that cultivar group, rather than the genetic origin (modern vs. landrace), is the major source of variation for all agronomic and quality traits. Batavia and Butterhead were highly homogeneous cultivar groups, while Cos accessions showed a much higher intra-varietal diversity. There was also a clear separation between modern and landrace varieties of Oak leaf. Fifteen out of the 16 landraces evaluated presented a high susceptibility to the particular B. lactucae race isolated from the experimental field - a new race not reported before. Breeding programmes intended to introgress genetic resistance to this pathogen are a major priority to recover the cultivation of lettuce landraces. Principal component analysis, conducted on all quantitative data, showed a clear differentiation between modern varieties and landraces, mostly related to their commercial weight and susceptibility to B. lactucae. These seem the most important traits influencing farmer and consumer evaluations. Farmers showed a high capacity for characterising the samples and agreed with consumers when scoring for the external appearance. It is proposed that farmers and consumers should be included in the phenotyping platforms in future research projects aiming for recovery of landraces.